Radioimmunotherapy of Fungal Diseases: The Therapeutic Potential of Cytocidal Radiation Delivered by Antibody Targeting Fungal Cell Surface Antigens - Nosanchuk, Joshua D.; Dadachova, Ekaterina (Frontiers in Microbiology, 2012)
Radioimmunotherapy is the targeted delivery of cytocidal radiation to cells via specific antibody. Although mature for the treatment of cancer, RIT of infectious diseases is in pre-clinical development. However, as there is an obvious and urgent need for novel approaches to treat infectious diseases, RIT can provide us with a powerful approach to combat serious diseases, including invasive fungal infections. For example, RIT has proven more effective than standard amphotericin B for the treatment of experimental cryptococcosis. This review will discuss the concepts of RIT, its applications for infectious diseases, and the strides made to date to bring RIT of infectious diseases to fruition. Finally, we will discuss the potential of PAN-FUNGAL RIT, the targeting of conserved fungal cell surface antigens by RIT, as a treatment modality for fungi prior to the formal microbiological identification of the specific pathogen. In sum, RIT provides a mechanism for the targeted killing of drug susceptible or resistant fungi irrespective of the host immune status and may dramatically reduce the length of therapy currently required for many invasive fungal diseases.